Enhancing Early Reading Skills in Students with Intellectual Disabilities: The Effectiveness of Contextual Learning-Based Interactive Animation Media - Armini, Armini; Purwanta, Edi (Journal of Innovation and Research in Primary Education, 2025)
Students with intellectual disabilities face significant challenges in early reading acquisition, requiring specialized instructional approaches that address their unique learning needs. This study investigated the effectiveness of contextual learning-based interactive animation media in improving early reading skills among first-grade students with intellectual disabilities. A quasi-experimental design was employed with three first-grade students with intellectual disabilities at SD Negeri 004 Sangkulirang, Indonesia. Participants completed pretest and posttest assessments measuring five reading components: letter pronunciation, syllable formation, word construction, simple word reading, and short sentence reading (maximum score: 80 points). A contextual learning-based interactive animation intervention was implemented, featuring familiar daily life contexts and interactive elements. Student experiences were assessed through questionnaires using 5-point Likert scales. Data analysis included descriptive statistics and prerequisite assumption testing. All participants demonstrated substantial and consistent improvements, achieving identical 25-point gains between pretest and posttest measurements. Mean scores increased from 40.0 to 65.0 points, representing a 62.5% improvement in overall reading performance. Student questionnaire responses indicated high satisfaction with interactive elements (mean: 12.0), content relevance to daily life (mean: 11.3), and visual/audio appeal (mean: 11.0). Statistical prerequisite tests confirmed data normality and homogeneity assumptions. The uniform improvement pattern demonstrates that contextual learning-based interactive animation media effectively addresses reading acquisition challenges in students with intellectual disabilities. The intervention's success stems from its integration of familiar contextual content, multi-modal presentation, and interactive engagement that prevents cognitive overload while facilitating meaningful knowledge construction. These findings extend constructivist learning theory and multimedia learning principles to inclusive education contexts, providing a replicable framework for developing educational technologies for students with learning differences.